Pengaruh Waktu Inokulasi Inokulum Dalam Pembuatan Bioetanol Dari Limbah Srabut Buah Sawit Menggunakan Saccharomyces Cerevisiae - Muria, Sri Rezeki; Firmanto, Firmanto; Ahmad, Adrianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bioethanol is produced with raw materials containing starch plant or carbohydrates (rice,  maize, tubers, etc.) and cellulosic materials (wood, agricultural waste), conducted through the conversion of carbohydrates into sugar (glucose) with the fermentation process by microorganisms. Bioethanol can be made as solvents, perfume ingredients, flavourings, food dyes and medications, even can be made as alternative fuels. Bioethanol production is done by the hidrolysis and fermentation or frequently called to SHF process (Separated Hydrolysis and Fermentation). Cellulose and hemiscellulose  to be used is sourced from palm fiber waste. The goal of this study is to obtain the effect of time of inoculation inoculum and also get the optimum concentration of  bioethanol in the manufacture of bioethanol from palm fruits fiber waste. Stages of the purification process starts from pretreatment, delignification with ash extract TKS and purification with hydrogen Peroxide (H2O2). After the purification process, the next stage is hidrolysis process with sulfur acid (H2SO4  2M). Hidrolysis was done at a temperature of 100 oC and a reaction time about 3 hours to get the initial glucose. The effect of inoculum time to be done in this study by the variaion of time 24, 48, 60 and 72 hours. Number of cells for the inoculum  will be analyzed with spectrophotometer by observing optical density (OD). Fermentation process will take place during 4,5 days (108 hours) by the variation of time 12, 24, 48, 72, 96 and 108 hours with the help of  Saccharomyces cerevisiae. The result showed that the best time of inoculum occurred at 60 hours with OD 0,882 with time of  fermentation at 96 hours which got the concentration of bioethanol 6 v/v (47,34 gr/L). Keywords: bioethanol, fermentation, hidrolysis, inoculum, palm fiber, Saccharomyces  cerevisiae